Factors Associated with Symptom Recurrence Following Operative Treatment of Interdigital Neuroma - Samir Ghandour MD; Emi R. Suyama BS; Evan Sirls; Jiyong Ahn MD, PhD; Bernard Burgesson MD; Lercan Aslan MD; Soheil Ashkani-Esfahani MD; Daniel Guss MD, MBA; Gregory Waryasz MD; Lorena Bejarano-Pineda MD; Christopher W. DiGiovanni MD (Foot & Ankle Orthopaedics)
Category: Midfoot/Forefoot; Trauma Introduction/Purpose: Interdigital Neuroma (IN) is a benign enlargement of tissue surrounding the common plantar digital nerve. Traditionally, neurectomy has been performed as the standard surgical treatment for IN. However, recent attention has been given to less invasive surgical decompression by intermetatarsal ligament (IML) release with neurolysis. This study aims to compare the outcomes of IML release with neurolysis to traditional interdigital neurectomy. Methods: A retrospective chart review was conducted on 350 consecutive patients who underwent surgical treatment for IN. Patients who satisfied our inclusion and exclusion criteria were categorized into two groups based on the surgical treatment received: IML release with neurolysis or interdigital neurectomy. Inclusion criteria were patients older than 18 years with symptomatic IN, having an indication for surgical treatment following at least three months of unsuccessful conservative treatment, and at least 12 months of postoperative follow-up. Patients with concurrent procedures at the time of surgery, multiple affected web spaces, trauma to the affected forefoot, or asymptomatic IN without clear indications for surgical treatment were excluded from the study. Evaluated outcomes included recurrence of symptoms, rate of revision surgery, and postoperative wound infection. Results: Out of the 350 patients screened, 127 fulfilled the inclusion and exclusion criteria. Forty (32%) patients experienced recurrence of symptoms within a 12-month follow-up period with an overall mean time-to-recurrence of 3.96 +/- 3.15 months. Patients who underwent IML release with neurolysis had a significantly higher recurrence rate (48%) and mean time-to-recurrence of 4.61 +/- 3.22 months compared to those who underwent interdigital neurectomy (24%) with a mean time-to-recurrence of 3.47 +/- 3.08 months (P< 0.01). The rate of postoperative wound infection was similar between the two groups. The rate of revision surgery among those with symptom recurrence in the IML release group (16%) and neurectomy group (4%) was not statistically significant between both groups (P=0.49). Conclusion: IML release with neurolysis appears to have a higher risk of symptom recurrence compared to interdigital neurectomy. However, patients who did experience symptom recurrence in either operative group had similar rates of revision surgery, which may be due to mild recurrent symptoms in the IML release group that did not warrant revision surgery in these patients. No patient-specific factors were identified as being associated with symptom recurrence. Future studies should consider objective symptom recurrence severity and patient satisfaction.